Reinforced Portland cement porous scaffolds for load-bearing bone tissue engineering applications. (2023)
Modified Portland cement porous scaffolds with suitable characteristics for load-bearing bone tissue engineering applications were manufactured by combining the particulate leaching and foaming methods. Non-crosslinked polydimethylsiloxane was evaluated as a potential reinforcing material. The scaffolds presented average porosities between 70 and 80% with mean pore sizes ranging from 300 µm up to 5.0 mm. Non-reinforced scaffolds presented compressive strengths and elastic modulus values of 2.6 and 245 MPa, respectively, whereas reinforced scaffolds exhibited 4.2 and 443 MPa, respectively, an increase of ~62 and 80%. Portland cement scaffolds supported human osteoblast-like cell adhesion, spreading, and propagation (t = 1-28 days). Cell metabolism and alkaline phosphatase activity were found to be enhanced at longer culture intervals (t = 14 days). These results suggest the possibility of obtaining strong and biocompatible scaffolds for bone repair applications from inexpensive, yet technologically advanced materials such as Portland cement.